Pengaruh Tingkat Stres Saat Kuliah Daring Terhadap Binge Eating Disorder - Hansel Filipi; Annisa Ullya Rasyida (Fakultas Kedokteran, Universitas Hang Tuah, 2022)
The outbreak of the Covid-19 virus in Indonesia in 2020 caused many changes in the government sector, work and even education. Online learning has several impacts from various sides, both for educators and on students, one of which is increased stress. Stress has various effects, one of which is eating disorder, therefore the researcher wanted to know whether there is an effect of stress level during online lectures on binge eating disorder. This research is an analytic observational study, with a cross sectional type. This study used a sample of 238 respondents, and the sampling used the quota sampling method. In taking the sample, the researcher used the DASS-42 and BES questionnaires, assisted by the google form instrument. Data processing was carried out statistically using = 0.05 and hypothesis testing using Spearman correlation. Measurement of stress levels showed that 159 respondents had normal stress levels, 38 respondents had mild stress levels, 23 respondents had moderate stress levels, 14 respondents had severe stress levels, and 4 respondents had very severe stress levels. In the measurement of binge eating disorder, there were 212 respondents with no/mild BED levels, 22 respondents with moderate BED levels, and 4 respondents with severe BED levels. The data above was tested for Spearman correlation, and obtained significant results (α = 0.000), where there is an influence between stress levels and binge eating disorder. The level of stress affects the severity of binge eating disorder, therefore it is necessary to do adequate stress management to avoid the possible effects of binge eating disorder, as well as the effects of other stress.